Re-Lock: Penerapan Integrasi Smart Lock Menggunakan Image Processing Berbasis Artificial Intelligence Menuju Indonesia Emas 2045 - Maharani, Mega; Suhafid, Muh. Zulhamdi (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2024)
Golden Indonesia 2045 is a long-term vision that targets Indonesia to become a developed country with high levels of welfare and security. One important aspect in achieving this vision is the application of advanced technology to support security and efficiency in various sectors. This article aims to discuss the application of smart lock integration using artificial intelligence (AI)-based image processing technology, called “Re-Lock”. Re-Lock technology is designed to enhance physical security through advanced visual identification, allowing access only to authorized individuals based on real-time image analysis. This research adopts a system development method that integrates AI with smart locks, where image processing is used to recognize faces, fingerprints, or certain patterns as a form of identity verification. Case studies were applied to smart home environments and public facilities to test the reliability and efficiency of the system under real conditions. The results show that Re-Lock has a high accuracy rate in identifying individuals and is able to significantly reduce the risk of unauthorized access. In addition, the system is also designed to be easily integrated with existing infrastructure, making it a practical and affordable solution in supporting national security in the digital era. The implementation of Re-Lock is projected to contribute significantly to the achievement of the Golden Indonesia 2045 vision, by making security technology one of the main pillars in the country's development.